Pedro Nava - cronista de uma época: medicina e sociedadebrasileira (1890-1940) - Vanda Arantes do Vale (2009)
Pedro Nava (1903-1983), Brazilian physician and writer, published six memoirs books between 1972 and 1983. The works Baú de ossos: memoir, Balão cativo: memoir 2, Chão de ferro: memoir 3, Beira-mar: memoir 4 , Galo das trevas: memoir 5 and O círio perfeito: memoir 6 add up approximately 2.500 pages. They draw a wide panel of the Brazilian society. The memorialist rebuilt his father´s scholar and professional path, the physician José Nava (1876-1911) in Baú de ossos: memoirs and his own in the other books. Pedro Nava´s memoirs work composes a documental source for studies related to medicine and Brazilian society (1890-1940).